Sistem Kelayakan Pendaftaran Dana KIP pada SMKS Dwiwarna Medan dengan Metode PSI: Array - Hutasuhut, Muhammad Rizki Hamdani; Tommy, Tommy; Budiman, Arief (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2021)
The Indonesian government through the Smart Indonesia Program provides cash assistance through the Smart Indonesia Card. The problem that occurs is that the selection process for KIP assistance recipients has not gone through the right procedure, resulting in social jealousy among students who should not be eligible to receive assistance but receive the KIP assistance funds. This is because some students have relatives from school officials so that student data can be manipulated. Therefore, a decision support system is needed that is able to select the eligibility of students receiving KIP funds quickly and accurately by using the Preference Selection Index (PSI) method. The Preference Selection Index (PSI) method which in line performs calculations on the matrix multiplication between criteria that have a weighted value of each alternative so as to produce a PSI value which will be the final result in determining the eligibility of students to receive KIP assistance funds. The resulting impact is the selection of students who really have the eligibility requirements to get KIP funding assistance.